Клинковое оружие XII – XV вв. с территории междуречья Верхнего Прута и Среднего Днестра - Возний, Ігор (Stratum plus. Культурная антропология. Археология., 2019)
I. P. Vozny The Blade Weapon of the 12th—15th Centuries from the Territory between the Upper Prut and the Middle Dniester The article deals with the most popular among the warriors offensive melee facilities weapons, especially swords, medieval sabres, falchions and their components found in the northern part of the Dniester-Prut interfluvial area. The territory of the Northern Bukovina knows 11 swords. The above analysis of blade weapons made it possible to distinguish among them some types of XIIa, XVIа, XVII, and XX according to E. Okshott, dating to 14th—16th centuries. The proposed typology is not exhaustive and definitive, and perhaps further research and new finds will be able to clarify it more. The fragments of the sabre, as well as the saber guards, were found on the studied area. The latter refers to types I, II according to A. Kirpichnikov. The guards are dated by the analogies of the 11th—13th centuries. Among the weapons found in the investigated territory, there are also known two falchions, of cross-guard shape and pommel shape. The falchions are type 1 and 2 according to A. Nadolsky. They are dated by the middle of the 15th — the beginning of the 16th centuries. Thus, it is obvious that the local population from the investigated territory was quite sufficiently armed. Evolution of these weapons was mainstreamed with the general development of the military art in Europe. The territory of the Northern Bukovina in the 12th—16th century was involved into the pan-European political events. And the finds of the advanced weapons of that time serves as evidences to the fact.
Keywords: Dniester-Prut area; Bukovina; Middle Ages; sword; sabre; guards; falchions; pointed or bladed weapon; horserider; warrior; melee